A feedback-based multiagent navigation framework - Loizou, Savvas; Kyriakopoulos, Kostas J. (My University, 2006)
In this paper, an on-line multirobot navigation methodology is presented, extending the concept of navigation functions from the single-point-sized holonomic robot domain to the domain of multiple non-point-sized holonomic robots. An appropriate measure of the distance from bad sets, suitable for multirobot navigation, is introduced. The derived closed form analytic solution provides a feedback-based navigation scheme, suitable for implementation, with theoretically guaranteed global convergence and collision avoidance properties. The proposed methodology is validated through non-trivial simulations. © 2006, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Centralized control; Multiple robots; Navigation functions; On-line planning